1992
DOI: 10.1056/nejm199211193272101
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Iron Chelation Therapy on Recovery from Deep Coma in Children with Cerebral Malaria

Abstract: Iron chelation therapy may hasten the clearance of parasitemia and enhance recovery from deep coma in cerebral malaria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
84
3

Year Published

1995
1995
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(88 citation statements)
references
References 18 publications
1
84
3
Order By: Relevance
“…DEF, a trihydroxamic acid siderophore produced by Streptomyces pilosus (40), is the only iron-chelating agent approved for clinical use. This drug has been used successfully as an adjunct in the treatment of malaria, in which it was found to hasten the clearance of parasitemia and enhance recovery from deep coma in patients with cerebral malaria (20). The only other iron chelator that has been extensively studied in humans is CP20, also known as L1 or deferiprone.…”
Section: Discussionmentioning
confidence: 99%
“…DEF, a trihydroxamic acid siderophore produced by Streptomyces pilosus (40), is the only iron-chelating agent approved for clinical use. This drug has been used successfully as an adjunct in the treatment of malaria, in which it was found to hasten the clearance of parasitemia and enhance recovery from deep coma in patients with cerebral malaria (20). The only other iron chelator that has been extensively studied in humans is CP20, also known as L1 or deferiprone.…”
Section: Discussionmentioning
confidence: 99%
“…6,[15][16][17][18] Most deaths occur within 24 hr of starting treatment 6,7,16,[19][20][21] and most of those who survive recover fully within 48 hr of starting treatment. 6,15,16,20,21 To be credible, theories of fatal malaria pathogenesis must explain the rapidity with which these syndromes develop and then either kill the patient or resolve, leaving only 9-12% of survivors with neurologic sequelae. 6,17,22 Malaria hyperpneic syndrome.…”
Section: Descriptionmentioning
confidence: 99%
“…26 Patients are excluded if they improve within 1 hr of a convulsion, or of being restored to a normoglycemic state. 6,7,15,16 A less stringent definition, where any impairment of consciousness is sufficient justification for intensifying the clinical management (parenteral antimalarials, assiduous nursing care) is more appropriate in usual clinical settings. 26 The neurologic manifestations of CM span the spectrum from diffuse cortical involvement to specific brainstem abnormalities.…”
Section: Descriptionmentioning
confidence: 99%
“…Studies in human malaria showed that DFO alone, or in combination with standard therapy, enhances parasite clearance in asymptomatic and severe malaria (Traore et al, 1991;Gordeuk et al, 1992;Mabeza et al, 1996). Continuous infusion of DFO over a 3 day period is required to obtain enhanced parasite clearance in human malaria (Mabeza et al, 1996).…”
Section: Discussionmentioning
confidence: 99%